2012
DOI: 10.1016/j.dnarep.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Y-family DNA polymerase Dbh in accurate replication of the Sulfolobus genome at high temperature

Abstract: The intrinsically thermostable Y-family DNA polymerases of Sulfolobus spp. have revealed detailed three-dimensional structure and catalytic mechanisms of trans-lesion DNA polymerases, yet their functions in maintaining their native genomes remain largely unexplored. To identify functions of the Y-family DNA polymerase Dbh in replicating the Sulfolobus genome under extreme conditions, we disrupted the dbh gene in Sulfolobus acidocaldarius and characterized the resulting mutant strains phenotypically. Disruption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…One hotspot matches the Dbh deletogenic motif closely (59 GCCCCC on the minus strand), whereas the other lacks the characteristic G (minus-strand 59 ATTTTTT). Both sites generate approximately equal proportions of +1 and 21 frameshifts in vivo (Grogan et al 2001;Sakofsky et al 2012), whereas purified Dbh makes 21 frameshifts almost exclusively (Potapova et al 2002). Thus the deletogenic activity exhibited by Dbh on undamaged DNA in vitro is consistent with some, but not all, of the observed properties of spontaneous mutation at these sites.…”
Section: No Detectable Contribution Of Dbh To Spontaneous Frameshift supporting
confidence: 67%
See 2 more Smart Citations
“…One hotspot matches the Dbh deletogenic motif closely (59 GCCCCC on the minus strand), whereas the other lacks the characteristic G (minus-strand 59 ATTTTTT). Both sites generate approximately equal proportions of +1 and 21 frameshifts in vivo (Grogan et al 2001;Sakofsky et al 2012), whereas purified Dbh makes 21 frameshifts almost exclusively (Potapova et al 2002). Thus the deletogenic activity exhibited by Dbh on undamaged DNA in vitro is consistent with some, but not all, of the observed properties of spontaneous mutation at these sites.…”
Section: No Detectable Contribution Of Dbh To Spontaneous Frameshift supporting
confidence: 67%
“…In vitro, Dbh and Dpo4 preferentially insert dC opposite 8-oxo-dG (Gruz et al 2001;Rechkoblit et al 2006;Zang et al 2006;Maxwell and Suo 2012); this predicts that these enzymes would suppress transversion in vivo if recruited to 8-oxo-dG during replication of Sulfolobus chromosomes. Consistent with this prediction, disrupting the dbh gene (Saci_0554) resulted in increased rates of spontaneous G:C-to-T:A transversions in a chromosomal gene (pyrE) where forward mutations can be selected (Sakofsky et al 2012).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…This demarcation of the primase/polymerase activities between PrimPol and Pri S probably reflects the additional replication requirements for much larger genomes, such as more regulated laggingstrand synthesis. Although some archaeal species possess canonical Y-family DNA polymerases (Dpo4), specialized in traversing DNA lesions, a recent study has reported that Sulfolobus strains lacking Dpo4 display no increased sensitivity to DNA damaging agents, including UV (32). This strain also exhibited no difference in rates of spontaneous mutagenesis, suggesting that other TLS pathways assist in bypassing replication-blocking lesions.…”
Section: Discussionmentioning
confidence: 95%
“…1A; Table 3). This behavior mimics that of spontaneous mutations in both the S. solfataricus and S. acidocaldarius pyrE genes, where similar motifs occur and account for similar slipped-strand events in the corresponding mutational spectra (3,22,23), albeit at much lower rates.…”
Section: Instability Of the Lacs Reporter Gene In Pjlacsmentioning
confidence: 83%